Reassessing ʿAjam in Arabic Discourse: Historical Semantics, Ethnolinguistic Othering, and Discursive Racialization Across Contexts - Muhammad Syafii Tampubolon; Rahmad Ilahi; Widiyanto; Zulkifli Hayad (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2026)
This study reassessed these competing interpretations using a qualitative, comparative, and diachronic research design that integrated historical-semantic analysis with Critical Discourse Analysis. The corpus comprised six classical and premodern Arabic sources and five modern academic or public-discourse sources selected using contrastive purposive sampling. Classical passages were analyzed for semantic reference, communicative function, ethnolinguistic reference, and evaluative meaning, whereas modern texts were coded for recontextualization, essentialization, hierarchy, moralization, and reclamation. The findings showed that the root ʿ-j-m was associated with opacity and limited linguistic clarity, whereas ʿAjam also functioned as an ethnolinguistic designation for non-Arabs and, in some contexts, Persians. The presence of pejoration and ethnolinguistic categorization did not, by themselves, establish racialization. Rather, racialization emerged when difference was essentialized, hierarchized, and ideologically framed within specific historical and political contexts. This distinction offers a more nuanced framework for examining the relationship between linguistic categorization, ethnolinguistic othering, and racialization in Arabic discourse.